Can online learners obtain sufficient competencies in the hospitality and tourism industries? - Sincharoenkul, Kris; Witthayasirikul, Chotima (Frontiers in Education, 2022)
The educational sector has been affected by the COVID-19 pandemic, such as the forced adaptation to online classes and students' lack of interaction and experience in practical classes. Because the hospitality and tourism industries require professional operations between guests and employees, this may cause concern among students who had to adapt to online classes during the pandemic about whether they have sufficient competencies to be recruited into the workplace. However, the internship benefits higher education institutions, industries, and students by examining the sufficiency of students' competencies in the workplace. Thus, this study aimed to determine the competencies of online learners that influence satisfaction in the employability of the hospitality and tourism industries post-COVID-19. The logistic regression models were established to predict the likelihood of competencies toward each satisfaction attribute. The empirical results showed that among five recruitment attributes, the competencies provided a predictor likelihood on three attributes: foundation, employability, and adaptability, while it had no likelihood on knowledge. The collaboration attribute reported the insignificant regression model. Moreover, only internship experience provided a significant result for the adaptive attribute. Moreover, the discussion and practical implications were provided in this study.